Dinamika Resiliensi dan Stres Pengasuhan pada Orang Tua Anak Berkebutuhan Khusus dalam Konteks Pendidikan Inklusi dan Sekolah Luar Biasa - Dilla Astarini; Angel Lita; Nada Larasaty Ayu Ningsih; Nadya Aulia Riftiani; Dita Hindriani; Nabila Dhara Alifah (Journal of Society Counseling, 2026)
This study aims to explore the dynamics of parenting stress and family resilience among parents of children with special needs (CSN) in inclusive schools and special schools (SLB) using a qualitative phenomenological approach. The findings show that stress and resilience emerge simultaneously in parenting experiences. In inclusive schools, stress is mainly related to social acceptance, children’s ability to adapt, and academic and social demands. In contrast, in SLB, stress is more focused on the child’s future independence, economic conditions, and long-term caregiving responsibilities. Resilience among parents in inclusive schools tends to be active, reflected in their involvement in school activities, parenting programs, and communication with teachers. Meanwhile, in SLB, resilience is shown through acceptance, emotional adjustment, and realistic expectations regarding the child’s independence. Theoretically, these findings highlight that parenting stress and resilience are dynamic, contextual, and interconnected processes. Practically, differentiated support services are needed to optimally support parents in each context.